Морфологічні особливості будови квітки видів роду Arctium L. (Asteraceae) - Sokol, O.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
A comparative analysis of flower structure of 4 species of the genus Arctium L. is made. Morphological and anatomical features that have taxonomic significance are reveal ed (wreath form, shape and spatial position of bending teeth, the color and spatial position stilodiya, apical loop anther epidermal cells wreath configuration). These features may be used as additional criteria for the characterization and identification of studied species.